Effectiveness of a program for the development of socio-emotional competences in people admitted to a penitentiary center - Granados, Lucía; Suriá, Raquel; Perea, Carles; Payá, Claudio; Sánchez-Pujalte, Laura; Aparisi, David (Frontiers in Public Health, 2023)
The purpose of this paper was to evaluate the effectiveness of a program for the development of social and emotional competences and self-esteem among a group of inmates at a penitentiary center, as well as to determine the possible correlation between the variables of the program (social skills, emotional competences, and self-esteem). The objective was to equip inmates with social competences in emotional regulation strategies that would be useful to them in the penitentiary center and, at the same time, facilitate their future social inclusion. In order to measure the pre- and post- treatment variables, the Social Skills Scale, the Perceived Emotional Intelligence Scale (TMMS-24), and the Rosenberg Self-Esteem Scale (RSES) were administered to a group of 51 inmates in a penitentiary center. The experimental group consisted of 29 inmates, with 21 forming the control group. The pretest-posttest ANOVAs showed that the program led to a significant (p < 0.01) increase in: (1) positive social behaviors; (2) emotional competences; (3) self-esteem. Positive correlations were also observed between the three variables. The results suggest the importance of implementing programs for the promotion of the socio-emotional development of people incarcerated in penitentiary centers.